Uji Daya Hambat Infusa Mahkota Bunga Rosella (Hibiscus sabdariffa L.) Terhadap Bakteri Escherichia coli dan Staphylococcus aureus - Hilda Sinaga (Herbal Medicine Journal, 2019)
Rosella (Hibiscus sabdariffa L.) is a plant from tropical and sub-tropical regions, including Indonesia. The purpose of this study was to determine the potential for roselle flower infusion (Hibiscus sabdariffa L.) to inhibit the growth of Staphylococcus aureus and Escherichia coli bacteria. This type of research is experimental research. In this study, the infusion of rosella flower crown was tested against Staphylococcus aureus and Escherichia coli bacteria. The process of making rosella flower crown infusion (Hibiscus sabdariffa L.) using aquadest solvent. Using the disc diffusion method to measure the clear zone in millimeters (mm) for bacteria. Antimicrobial inhibition of rosella flower crown infusion (Hibiscus sabdariffa L.) against Staphylococcus aureus bacteria at a concentration of 75%; 50%; 25% and 12.5% ​​had an inhibition zone diameter of 12.7 mm; 10.5 mm; 7.8 mm and 7 mm. Antimicrobial inhibition of rosella flower crown infusion (Hibiscus sabdariffa L.) against Escherichia coli at a concentration of 75%; 50%; 25% and 12.5% ​​had an inhibition zone diameter of 12 mm; 11 mm; 7.5 mm and 6.6 mm. The results of the phytochemical screening carried out in this study showed that the roselle flower crown (Hibiscus sabdariffa L.) contained flavonoids, saponins, and tannins. These results indicate that the infusion of roselle flower (Hibiscus sabdariffa L.) has antibacterial activity against Staphylococcus aureus and Escherichia coli bacteria.